Impact of infestation by parasitic weeds on rice farmers' productivity and technical efficiency in sub-Saharan Africa - Ncho, S.A.; Mourits, M.; Demont, M.; Adegbola, Patrice Ygue; Lansink, A.O. (2017)
Rice production is crucial for food security and income generation in sub-Saharan Africa. However, productivity and technical efficiency levels in rice production systems are severely constrained by biotic constraints such as parasitic weeds. This paper assesses the impact of infestation by parasitic weeds on rice farmers’ technical efficiency and examines the potential role of managerial factors in improving technical efficiency. Household and field survey data were collected from rice farmers in Cote d’Ivoire and Benin in West Africa. A stochastic frontier production function was estimated, which allows for identifying the levels of exogenous factors that prevent farmers from improving technical efficiency levels. The results suggest that farmers cope with parasitic weeds through learning from experiencing infestations by parasitic weed. The results will assist national extension in designing segmented training programmes that are better tailored to rice farmers’ needs and preventing food security from being jeopardized by parasitic weeds.